Primary Closure versus T-tube Drainage in laparoscopic Choledocholithotomy - Rahman, Md Mostafizur; Hossain, Md Shakhawat; Ahsan Shahid, Shah Md (TAJ: Journal of Teachers Association, 2023)
Introduction: Choledocholithotomy followed by T-tube has long been a standard surgical treatment for choledocholithiasis. It is still a preferred choice in many hospitals where minimally invasive procedures are not feasible. The use of T-tube is not without complications. To avoid complications associated with T-tube, we have performed primary closure of the common bile duct (CBD) after exploration. This pilot study assessed the safety of primary closure of CBD, which would help form a basis for implementation on a wider scale. Aim of the study: To compare the outcome in primary closure of the common bile duct and T-tube drainage after choledocholithotomy. Methods: This cross-sectional study was conducted in the Department of Surgery at IBNSina Medical College &Hospital, Dhaka, and Delta Medical College& Hospital, Dhaka Bangladesh; from January 2021 to December 2022. A total of 80 patients were selected purposively, and were randomly divided into two groups: The t-tube drainage group and the primary closure group. Each group consisted of 40 patients. Data were entered and analyzed using SPSS software. Ethical clearance was obtained from the hospital's ethical review committee. Result: The most common presentation in the primary closure group was jaundice with 18 patients (45%) but most of the patients in the T-tube group presented with acute cholecystitis with 21 patients (52.5%).In primary closure patients the mean operating time was observed to be 60±15mins while that in the case of T-tube drainage patients was 90±10 mins. The total duration of hospital-stay in primary closure patients ranged from 6-10 days with an average duration of 8 days which was much shorter than that of T-tube drainage patients which ranged from 10-16 days with an average of 13 days. Conclusion: Primary closure following laparoscopic CBD exploration is safe and feasible for selected patients with choledocholithiasis. TAJ 2023; 36: No-2: 65-70